In Puruchuco is destroyed archaeological heritage of Peru - Bueno Mendoza, Alberto (2014)
The archaeological site of Puruchuco occupies all areas of Cerro Mayorazgo whose studies by archaeologists indicate that such dierent occupations belong to dierent archaeological periods of ancient Peru. Archaeological evidence found at the view from the north ridge, the eastern ank of the hill, the truncated and in several areas of its western slope, whose lower parts are being discovered the next archaeological evidence to Site Museum and the Grand Palace summit Tawantinsuyu rescued and put in value by Dr. Arturo Jiménez Borja (1956-1961).